Availability and Utilization of Digital Resources for Entrepreneurship Skills Acquisition in Business Education Program in Colleges of Education in Anambra State - Chinwe Mikella Nebolisa (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: Digital resources have become pivotal in enhancing teaching and learning, particularly in entrepreneurship education. In Nigeria, integrating such resources into Business Education programs is crucial for equipping students with relevant entrepreneurial skills. Objective: This study aimed to investigate the availability and utilization of digital resources for entrepreneurship skills acquisition among final-year Business Education students in Colleges of Education in Anambra State, Nigeria. Method: A structured questionnaire was used to collect data from a sample of 80 final-year students via Google Survey. The questionnaire addressed digital resource availability, usage patterns, and challenges. Hypotheses were tested using Analysis of Variance (ANOVA) to examine gender differences and the effect of digital resource availability on skill acquisition. Result: Findings revealed that while e-books and online platforms are accessible and integrated into the program, significant challenges remain. These include limited access to high-quality digital materials and persistent issues with internet connectivity, which hinder effective utilization. Conclusion: The study highlights a partially effective integration of digital resources into Business Education programs. To enhance entrepreneurship skill acquisition, it is essential to overcome the identified barriers. Contribution: This study contributes to the discourse on digital education in Nigeria by identifying critical gaps in digital resource availability and utilization. It provides actionable insights for policymakers, educators, and administrators aiming to strengthen entrepreneurship training through improved digital infrastructure and resource access.